A Single‐Source Precursor Approach to Self‐Supported Nickel–Manganese‐Based Catalysts with Improved Stability for Effective Low‐Temperature Dry Reforming of Methane. Issue 4 (25th February 2016) - Menezes, Prashanth W.; Indra, Arindam; Littlewood, Patrick; Göbel, Caren; Schomäcker, Reinhard; Driess, Matthias
Abstract: Self‐supported nickel–manganese‐based catalysts were synthesized from heterobimetallic nickel manganese oxalate precursors via a versatile reverse micelle approach. The precursors were subjected to thermal degradation (400 °C) in the presence of synthetic air to form respective metal oxides, which were treated under hydrogen (500 °C) to form Ni2 MnO4 –O2 –H2, Ni6 MnO8 –O2 –H2 and NiO–O2 –H2 . Similarly, the precursors were also treated directly under hydrogen at the same temperature to form Ni2 MnO4 –H2 and Ni6 MnO8 –H2 . The catalysts were extensively investigated by PXRD, SEM, TEM, XPS and BET analyses. The resulting catalysts were applied for dry reforming of methane (DRM) and exhibit better stability and resistance to coking than coprecipitated catalysts. Further, we show that addition of manganese, which is not an active catalyst for DRM alone, to nickel has a significant promotion effect on both the activity and stability of DRM catalysts, and a Ni/Mn ratio lower than 6:1 enables optimized activity for this system. Abstract : A perfect combination : The ratio of nickel and manganese within the single‐source precursors used to prepare NiMn catalysts controls the subsequent catalytic efficiency in the low‐temperature dry reforming of methane (see figure).